Simulation of hydrogen production for mobile fuel cell applications via autothermal reforming of methane - Abd. Hamid, Mohd. Kamaruddin; Ibrahim, Norazana; Ibrahim, Kamarul Asri; Ahmad, Arshad (2006)
This paper presents a simulation of catalytic autothermal reforming (ATR) of methane (CH4) for hydrogen (H2) production. ATR is essentially an oxidative steam reforming, which combines the exothermic partial oxidation (PO) with the endothermic steam reforming (SR) under thermally neutral conditions. A model is developed using HYSYS 2004.1 to simulate the conversion behavior of the reformer. The model covers all aspects of major chemical kinetics and heat and mass transfer phenomena in the reformer. The ATR and preferential oxidation (PrOx) processes is modeled using conversion reactor, while the water gas shift (WGS) process is modeled using equilibrium reactor within HYSYS environment. The conditions used for high CH4 conversion and high H2 yield are at air to fuel ratio of 2.5 and water to fuel ratio of 1.5. Under this condition, CH4 conversion of 100% and H2 yield of 44% on wet basis can be achieved and the system efficiency is about 87.7%.